CONJUNCTION OF POLITICAL COLUMN OF THE JAKARTA POST - Nurul Husnah Harahap; Dwi Pebrina Sinaga; Marlina br Tampubolon (Sean Institute, 2023)
This study deals with the use of conjunctions in political column of The Jakarta Post. The objectives of the study were to find out the types of conjunction was used in the political column of The Jakarta Post and to find out the most dominant conjunction used in the political column of The Jakarta Post. A library research was conducted to analyze the use of conjunctions. The data were analyzed by applying descriptive qualitative design. The data of the study covers 14 texts of seven editions published on every week for seven weeks from 23rd June 2014 until 10th August 2014 in political column of The Jakarta Post. Techniques for collecting data were selecting the text from the political column, reading the sentences accurately and underlying the conjunctions in each sentences of the political column. Techniques for analyzing data were identifying the types of conjunction, determining the sentences into the types of conjunction and counting the most dominant types of conjunction in the political column of The Jakarta Post. There were three types of conjunctions, they are (1) Coordinating Conjunction, (2) Subordinating Conjunction and (3) Correlative Conjunction. There were 251 sentences in the texts. Types of conjunction were found that coordinating was 260 (57%), subordinating was 182 (40%) and correlative was 13 (3%). The most dominant types of conjunction was coordinating 260 (57%) from the total of conjunction occurrences of seven publications in the political column of The Jakarta Post.